Work ability in hospital housekeeping services and associated factors - Marlize Tatsch Beltrame; Tânia Solange Bosi de Souza Magnago; Ana Lúcia Cardoso Kirchhof; Cintia da Silva Marconato; Bruna Xavier Morais
This study aimed to measure the Work Ability Index of workers of a hospital housekeeping staff and identify the associated factors. Cross-sectional study conducted in 201 with 157 workers of the housekeeping staff of a university hospital in Rio Grande do Sul, Brazil. A questionnaire containing sociodemographic, labor and health variables and the Brazilian version of the Work Ability Index was used. As a result, 79.6% of the workers were classified as having good/great work capacity. Mild mental (31.8%) and musculoskeletal disorders (15.9%) were the most prevalent medical diagnoses. After some adjustments, the workers that did not have time for leisure showed a 2.67 times higher prevalence of having the work ability reduced (CI95%=1.23-5.82). The other variables lost their association with the outcome. Measures aimed at the maintenance of work ability and the practice of physical activity and training for postural care are indicated.